Go ahead and trade: The effect of uncertainty removal in the EU's GSP scheme - Ingo Borchert; Mattia Di Ubaldo (The Economic and Social Research Institute (ESRI), 2020)
We estimate the trade effect of removing uncertainty about future trading conditions in the context of the 2014 reform of the Generalized System of Preferences (GSP) of the European Union (EU). EU GSP members receive non-reciprocal trade preferences (NRTPs), but only as long as they are not too competitive; i.e. they will graduate in case their share of EU GSP imports in a sector exceeds a certain threshold. However, the 2014 reform removed the threat of these competitiveness-related graduations for members of the so-called "GSP+", a sub-scheme of the main programme. We find that the reform increased EU imports from GSP+ countries by about 45% on average whilst tariffs stayed the same. This trade impact is driven by the country-sector pairs most exposed to NRTPs uncertainty prior to the reform. The effect is robust to taking into account other aspects of the reform, such as the reduction in GSP membership and changes in tariff margins, respectively.
Keywords: F13; F14; 330; GSP; trade preferences; trade policy uncertainty